Ecological Perspective on Avian Faunal Diversity of Kibber Wildlife Sanctuary, Trans-Himalayan Region, Himachal Pradesh, India - Banyal, Harinder Singh; Sharma, Archana (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
It has long been known that the trans-Himalayan region of Himachal Pradesh, India is home to the remarkable biodiversity. The findings in this research paper constitute an important addition to the knowledge of ornithology in Kibber Wildlife Sanctuary. This study gives insight into the habitat preference of bird species in the sanctuary including estimation of their migratory patterns based on altitude and analysis of IUCN status in accordance with field observations. For this meadows, pastures, few waterlogged habitats in the sanctuary were taken into consideration while using both point count as well as random sampling methods. The thorough investigation on said aspects will offer more information related to this landscape in near future. Also, present findings will help in the sanctuary's management plans and efforts to conserve biodiversity.